Preliminary Study on the Suitability of the Installation of Wind Solar Hybrid Off-Grid Energy System in Peninsular Malaysia - Chiang, Wan Qin; Nurul Aini, Osman (2016)
There were varies of renewable energy technologies available in market but these two types namely solar and wind have attracted more attention as wind and solar renewable energy systems can be set up as autonomous or stand-alone. Wind-solar hybrid system is the complementarily between the solar energy and the wind energy which one of the energy sources would offset shortfall of the other and produce significantly to meet the energy demand. Wind Solar Hybrid off-grid Energy System counted as a best hybrid model which compensate each other while create the expectation outcomes. The perceptions of the renewable energy authorities in Malaysia were interviewed and weather data been collected in order to detect the suitable location for implementation of this system. Based on the analysis of the findings, we found out that Wind Solar Hybrid off-grid Energy System consider having the potential possibility suitable installation in Peninsular Malaysia. Mersing, Johor had been identified as high potential condition to install this type of energy system. However, there were some barrier requirement such as size of land and capability of wind energy that need to be consider before installing the Wind Solar Hybrid off-grid Energy System. Awareness of hybrid energy system has been discover and attract attention by those energy department under government of Malaysia through this research.